The role of musical self-concept and embodiment in stress and flourishing among Chinese university music students - Yu, Xia; Xu, Fumei (Frontiers in Psychology, 2025)
This study explores the embodied role of musical self-concept in the relationship between academic stress and flourishing among Chinese university music students. Music students face distinctively high levels of academic stress due to intensive practice schedules, performance anxiety, and demanding technical and creative assessments, all of which engage both their physical and psychological selves. Flourishing, defined as the integration of emotional, psychological, and social wellbeing, is essential for positive psychological health. Our sample consisted of 1,767 Chinese university music students. The findings reveal that academic stress has a significant and negative impact on flourishing, consistent with the literature on the harmful effects of stress on well-being. This study further identifies that the embodied nature of musical self-concept, particularly the emotional and communicative dimensions, significantly mediates the relationship between academic stress and flourishing. In contrast, the ability and ambition component did not show a significant mediating effect. The embodied aspects of musical self-concept are evident in the ways students physically engage with their instruments, experience emotions during performance, and integrate their sense of self into their musical practice. These results highlight the importance of cultivating a positive and embodied musical self-concept to counteract the detrimental effects of academic stress and foster flourishing. Interventions aimed at enhancing embodied musical practices and self-awareness may be particularly effective in supporting students’ overall wellbeing. This research contributes to a deeper understanding of the psychological and embodied dimensions that influence the wellbeing of music students, offering practical implications for educational strategies to enhance their flourishing.